EVALUATING SERVICESCAPE OF THE PREMIERE CINEPLEX 21 GROUP IN MANADO TOWN SQUARE 3 USING IMPORTANCE AND PERFORMANCE ANALYSIS - Rumokoy, Farlane S.; Sumampouw, George G. (Journal of Asean Studies on Maritime Issues, 2017)
As a part of ASEAN, Indonesia should be ready to face the open competition in ASEAN Economic Community. As a country with big number of population Indonesia of course considered as a promising goal for foreign company that intent on expand their business. Appearanced of The Premiere movie theaters in Manado become a phenomena although this kind of movie theater already introduced by other company that provide premium movie theater. This research aims to evaluate the servicescape of The Premiere Cineplex 21 Group in Manado Town Square 3. Type of this research is descriptive with quantitative approach and IPA used as the measurement tool. The sample size of this research is 100 respondents who already experience watching movie in The Premiere Cineplex 21 Group in Manado Town Square 3. Convenience sampling was used to collecting data through online questionnaire.The result, the servicescape of The Premiere Cineplex 21 Group in Manado Town Square 3 shows, the cleanliness of the toilet attribute located in Quadrant 2. On the other hand, electric seats inside the studio attribute placed in Quadrant 3 on IPA chart about servicescape of The Premiere Cineplex 21 Group in Manado Town Square 3. The Premiere needs to improve all of them in order to keep the market share they have already created otherwise to keep satisfying their customers, and creating further repatronage intention.Keywords: Cineplex 21 group, importance and performance analysis, leisure service settingservicescape, the premiere